Yoga for hypertension management in the UK – what is the evidence? - Nalbant, Gamze (2024)
Yoga is an ancient Indian philosophy and way of life that is being used as a means to improve health and well-being. Numerous studies have shown that yoga has positive effects on managing many non-communicable diseases. Moreover, growing evidence suggests that yoga could be used to improve the management of hypertension in addition to current management strategies. Yoga has also become increasingly popular in the world and the UK for improving health and well-being, and previous cross-sectional studies have reported that hypertension is one of the most commonly disclosed health conditions in yoga sessions in the UK. The popularity of yoga has surged globally, including in the UK. However, the term "yoga" encompasses a broad range of concepts and previous systematic reviews included studies from across the world including places where yoga could mean different things. Despite the increasing body of evidence supporting yoga's benefits for hypertension and overall well-being, research specifically focusing on yoga in the UK remains limited. This thesis aimed to bridge this gap by exploring the current landscape of yoga practice in the UK and its potential for managing hypertension. Three studies were conducted for this purpose, aiming to gain a comprehensive understanding of the provision of yoga in the country.